Application of numerical calculation to simulation analysis of stray current corrosion in radiator of HVDC Converter Valve. Issue 6 (March 2020) - Cui, Pengfei; Guan, Shengli; Guo, Jianbao; Wang, Guangwu; Wang, Haijun; Chen, Jianye; Huang, Kefeng; Geng, Man; Yang, Weiwong; Deng, Longlong
Abstract: According to the electrical structure design of the converter valve, the stray current scattered in the water path of the converter valve tower is coupled in the internal waterway of the aluminum radiator. It promotes the occurrence of corrosion on the inner surface of the waterway. However, due to the wide range of stray current in the valve tower distribution pipe, many factors affecting the properties of fluid and the actual engineering not allowed to be measured, and so on. For a long time, the corrosion of converter valve radiator has always been an urgent technical problem to be solved in the field of DC transmission. It has received extensive attention in various research institutions around the world. In this paper, according to the distribution pipe of 500kV light-triggered converter valve tower, the structure model and equivalent circuit model of the water path are built and the mechanism of stray current corrosion of aluminum radiator is analyzed. At the same time, the circuit simulation software is used, and according to Faraday's law, the stray current, corrosion rate and annual corrosion rate of aluminum radiator in distribution pipe were calculated quantitatively. According to the numerical calculation results, the corrosion of aluminum radiator is compared with that of actual engineering aluminum radiator, the primary and secondary relationship of stray current corrosion in aluminum radiator corrosion is put forward, which provides the basis and reference for system optimization and engineering transformation.